Speed of the internationalization process: The role of diversity and depth in experiential learning - Casillas, José C; Moreno-Menéndez, Ana M (Journal of international business studies, 2014)
By analyzing internationalization as a dynamic process, we attempt to explain the speed of international operations in terms of learning acquired in the course of past international activities. We consider that the speed of the internationalization process depends on the type of experiential learning that results from decisions implicit in the internationalization process: choice of location and modes of operation. Firms develop two types of learning activities with respect to the selection of foreign markets and modes of operation: diversity and depth of accumulated international activities. We propose that depth of international activities has an inverted U-shaped impact on the speed of the internationalization process, while diversity of international activities has a U-shaped influence on the speed of internationalization process. The results of our longitudinal study of 889 firms over 23 years (1986-2008) suggest that diversity of international activities promotes long-term learning by exposing the firm to richer experiences, although such learning only takes place over time. Depth of international activities may accelerate the internationalization process in the short term, but it eventually restrains its potential for development in the long term. Our research highlights the short-term vs long-term consequences of different types of decisions related to the internationalization process.